The ambiguous effect of minimum wages on workers and total hours - Eric Strobl; Frank A. Walsh (University College Dublin, UCD School of Economics, 2007)
We model a standard competitve labour market where firms choose combinations of workers and hours per worker to produce output. If one assumes that the scale of production has no impact on hours per worker, then the change in the number of workers and hours per worker resulting from a minimum wage are inversely related, We also demonstrate that total hours worked at the firm may rise if there are small fixed costs to hiring workers.
Keywords: J22; J38; 330; minimum wages; hours; employment; Arbeitsmarkt; Mindestlohn; Arbeitszeit; Arbeitskräfte; Personalkosten; Theorie